Let [x] = x2 − 2. If [2] − [x] = x2, then x =
Replies to This Thread: 1
|
----
Let [x] = x2 − 2. If [2] − [x] = x2, then x =
Posted: 10/08/2013 12:34
I'm confused with how you got to 2-(x^2-2)=x^2.
I attached how far I got before I began to get stuck. I need to brush up on factoring I think?
Contributor
Reply 1 of 1
Replies to This Thread: 0
|
----
Posted: 10/08/2013 16:04
Tiffany, here is the continuation of what you worked out. You need to factor the minus sign into the parentheses (x^2-2).
Replies to This Thread: 1
|
----
Let [x] = x2 − 2. If [2] − [x] = x2, then x =
Posted: 10/20/2013 13:29
How do you get from x^2-2 in the first step to x^2+2 in the second step? I just don't understand why the jump from - to + ?
Contributor
Reply 1 of 1
Replies to This Thread: 0
|
----
Posted: 10/20/2013 18:47
Pamela, we simply multiplied the negative sign, which you should think of like -1, into the parentheses.
So, for example: -(x-y) = -1*(x-y)=-x+y
Replies to This Thread: 0
|
----
Let [x] = x2 − 2. If [2] − [x] = x2, then x =
Posted: 10/20/2013 20:20
Thanks very much for clarifying, I'm very rusty even at basic math laws right now. Much appreciated.